Development of an in vitro approach to point-of-contact inhalation toxicity testing of volatile compounds, using organotypic culture and air-liquid interface exposure. (December 2020) - Mistry, Artik; Bowen, Larry E.; Dzierlenga, Michael W.; Hartman, Jessica K.; Slattery, Scott D.
Abstract: In vitro chemical risk assessment using human cells is emerging as an alternative to in vivo animal testing with reduced costs, fewer animal welfare concerns, and the possibility of greater human health relevance. In vitro inhalation toxicity testing of volatile compounds poses particular challenges. Here we report our efforts to establish a testing protocol in our own lab using the EpiAirway bronchial epithelium cell culture model and the Vitrocell 12/12 system for air-liquid interface (ALI) exposures. For purposes of method development, we used methyl iodide (MeI) as a test compound. We examined viability, cytotoxicity, and epithelial integrity responses. Dose-dependent, reproducible responses were observed with all assays. EpiAirway and BEAS-2B cytotoxicity responses to acute exposure were roughly similar, but EpiAirway was more resistant than BEAS-2B by the viability measurement, suggesting a proliferative response at low MeI concentrations. If wells were sealed to prevent evaporation, in-solution MeI concentration-response could be used to predict the response to MeI vapor within 2-fold by converting from the media- to the air-concentration at equilibrium using the blood:air partition coefficient for MeI. The long-term stability of EpiAirway cultures enabled repeated exposures over a 5-d period, which produced responses at lower concentrations than did acute exposure. Highlights: In vitro concentration-responses to MeI vapor treatment were compared between culture types, exposure routes, and assays. In vitro response to MeI vapor could be approximated from response to MeI solution, assuming air-medium equilibrium. Repeated ALI exposure of EpiAirway cultures to MeI vapor caused decreases in TEER not seen with acute treatment.